Polissacarídeos biodegradáveis úteis para a preparação de sistemas de liberação controlada de fármacos. Parte 1: Quitosana - Lucinda-Silva, Ruth Meri [UNESP]; Evangelista, Raul Cesar [UNESP] (My University, 2002)
Due to an increasing interest, a vast number of biodegradable polymers have been obtained recently. Polymers naturally produced, such as cellulose, starch, chitosan and alginate, represent biodegradable materials, with low toxicity and low cost. Among polysaccharides, chitosan has been of great interest of the industrial and academic research, due to its special qualities of biodegradability and biocompatibility and, on the other hand, to the versatility of its use in several physical forms and products. A significant growth in the development of new dosage forms capable to deliver the drug in a controlled and targeted way has been observed in these last years. Such pharmaceutical forms search, mainly, the reduction of the dose administered and of the administration frequency, the reduction of adverse side effects and, consequently, a better patient compliance. The present paper describes the use of chitosan in pharmaceutical products, especially in drug controlled delivery systems.
Biodegradable polysaccharides useful for the preparation of controlled drug delivery systems. Part 1: Chitosan
Keywords: Biodegradable polymers; Chitosan; Drug controlled delivery; Polysaccharides; alginic acid; cellulose; chitosan; polymer; polysaccharide; starch; biocompatibility; biodegradation; controlled drug release; drug cost; drug delivery system; drug dosage form; human; patient compliance; review; side effect